Analysis of Factors Affecting Customer Loyalty at PT. Semen Tonasa, Tbk in Palopo City - Edi Indra Setiawan; Evi Surahman; Burhan Rifuddin (IAIN Palopo, 2020)
This study aims to determine the influence of marketing stimulus factors (price factors, product factors, promotion factors and brand factors) to influence customer loyalty at PT. Semen Tonasa, Tbk in Palopo City. The population in this study The population in this study were all customers of PT. Semen Tonasa Tbk in the last 5 years until this research was conducted. Meanwhile, in this study, the samples taken by the researchers were the retailers of PT Semen Tonasa Tbk in Palopo City. The sampling technique uses incidental techniques with due regard to the sample criteria. While the method of data collection is through observation, interviews, commissioning. The data analysis method used is multiple regression with five variables. The results showed that Fhit> Ftab (6,041> 3.06). This means that simultaneously the marketing stimulus factors (price, product, promotion and brand) have a significant effect on customer loyalty. This means that the proposed hypothesis is accepted. Meanwhile, only partially product factor which is a marketing stimulus has a significant positive effect. This can be seen in the t test, namely the calculated value of X2 exceeds the table value (4.172> 2.131).